HIV treatment-as-prevention research at a crossroads - Bärnighausen, Till; Eyal, Nir M.; Wikler, Daniel (PLoS medicine, 2014)
In light of changing WHO guidelines for HIV treatment, Till BÃ¤rnighausen and colleagues consider how large-scale HIV treatment-as-prevention trials can be adapted so that they can remain viable. Please see later in the article for the Editors' Summary